Theoretical Analysis of Thermal Equilibration in a Rotating Solid Sphere Partially Immersed in a Hot Fluid: A Study Inspired by the Onde Cooking Process - Rodika Utama; Moh. Toifur; Ishafit Ishafit; Devi Farah Dina (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
This study presents a theoretical analysis of thermal equilibration in a sphere rotating with a constant angular velocity, where part of the sphere is submerged in a hot fluid and the other part is exposed to air. The model is inspired by the traditional onde-onde cooking process, which illustrates temperature equalization through continuous rotation during heating. By applying the steady-state heat equation in spherical coordinates and imposing boundary conditions representing two temperature regions (the hot fluid at T1 and the air at T2), the criterion for rotational equilibrium is obtained. The result shows that the angular velocity must satisfy the minimum threshold ωmin=k/ρcR2, where k is the thermal conductivity, ρ is the density, c is the specific heat, and R is the radius of the sphere. When the actual rotation rate exceeds this limit, the temperature distribution becomes nearly uniform, and the entire sphere approaches thermal equilibrium. The findings clarify the physical mechanism through which rotation enhances temperature uniformity in partially immersed solids. Beyond its culinary analogy, the model offers valuable insight for rotating heat exchangers, industrial drying systems, and thermal homogenization in composite materials.